2007
DOI: 10.1108/09564230710778137
|View full text |Cite
|
Sign up to set email alerts
|

Modeling service encounters and customer experiential value in retailing

Abstract: Purpose -The purpose of this study is to explore the impacts of service encounters on customer experiential value and subsequently on customer behavioral intentions in a shopping mall context in Taiwan. Design/methodology/approach -Data were gathered using mall intercepts at three large shopping malls in northern Taiwan. Structural equation modeling was employed to assess the proposed research model empirically. Findings -The empirical results revealed that: personal interaction encounters positively influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(113 citation statements)
references
References 50 publications
7
94
0
12
Order By: Relevance
“…These customers preferred shopping in large retail shoes store with music being played in the shop. We can find in past studies that music have significant impact on purchase intentions and mood of the audience (Keng et al, 2007;Alpert and Alpert, 2006;Baker, 1987). In this study it was found ISSN 2161-7104 2014 www.macrothink.org/jpag that spacious, neat and clean atmosphere of shop affect utilitarian shoppers' level of intention to patronize, money spent and time ( Jin and Kim, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These customers preferred shopping in large retail shoes store with music being played in the shop. We can find in past studies that music have significant impact on purchase intentions and mood of the audience (Keng et al, 2007;Alpert and Alpert, 2006;Baker, 1987). In this study it was found ISSN 2161-7104 2014 www.macrothink.org/jpag that spacious, neat and clean atmosphere of shop affect utilitarian shoppers' level of intention to patronize, money spent and time ( Jin and Kim, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This image attraction which consists of elements like décor, music, lighting, interior architecture, furniture, cleanliness and display (Baker, 1987) is advantageous and profitable for the retailers. All these environmental factors influence customers' perceptions about the quality of product (Baker, 1987) and depending on the functional needs of customers, they arouse attraction in them ( ElSayed et al, 2003) which shows a positive connection between the external environment and customers (Kim, 2002;Keng et al, 2007). This environmental stimuli influence purchase intentions of customers by creating positive attitudes in them (Bitner, 1992).…”
Section: In Store Display and Purchase Intentionmentioning
confidence: 99%
“…(1) Extrinsic versus intrinsic value; (2) Active versus reactive value; and (3) Self-versus other-oriented value (Keng et al, 2007).…”
Section: Perceived Value Customer Compliant and Customer Loyaltymentioning
confidence: 99%
“…A retrospective examination of past studies of shopping environment service quality shows that the appraisal indicators used all fall broadly within the five service package attributes identified by Fitzsimmons & Fitzsimmons: (1) Supporting facilities: This covers "hardware" infrastructure and facility indicators such as "transportation to the mall," or "cleanliness of shops" (Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Liu et al, 2008;Keng et al, 2007); (2) Facilitating goods: This aspect covers the quality of the goods being sold, including the range of products and brands available, the frequency with which new models are introduced, price, reliability, etc. (Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Keng et al, 2007;Liu et al, 2008); (3) Information: This includes the language and communication skills of the sales personnel, the presentation of information relating to the shopping facility, and visual merchandising (Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Liu et al, 2008); (4) Explicit service: This covers the attitude and professionalism of the sales personnel (Milliman, 1986;Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Keng et al, 2007;Liu et al, 2008), waiting time (Hui et al, 1997;Heung & Cheng, 2000), payment methods (Heung & Cheng, 2000), etc. ; (5) Implicit service: This aspect includes shopping facility décor, music, color schemes, and scent (Milliman, 1982;Bellizzi et al, 1983;Yalch & Spangenberg, 1990;Bellizzi & Hite, 1992), the aesthetic appeal or special features of the building in which the shopping facility is located (Kotler, 1974;Jansen-Verbeke, 1991;Bitner, 1992;Lin,...…”
Section: Service Packages and Service Qualitymentioning
confidence: 99%
“…(Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Keng et al, 2007;Liu et al, 2008); (3) Information: This includes the language and communication skills of the sales personnel, the presentation of information relating to the shopping facility, and visual merchandising (Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Liu et al, 2008); (4) Explicit service: This covers the attitude and professionalism of the sales personnel (Milliman, 1986;Heung & Cheng, 2000;Yuksel, 2004;Josiam et al, 2005;Keng et al, 2007;Liu et al, 2008), waiting time (Hui et al, 1997;Heung & Cheng, 2000), payment methods (Heung & Cheng, 2000), etc. ; (5) Implicit service: This aspect includes shopping facility décor, music, color schemes, and scent (Milliman, 1982;Bellizzi et al, 1983;Yalch & Spangenberg, 1990;Bellizzi & Hite, 1992), the aesthetic appeal or special features of the building in which the shopping facility is located (Kotler, 1974;Jansen-Verbeke, 1991;Bitner, 1992;Lin, 2004;Keng et al, 2007), and the sense of excitement, discovery or cultural enlightenment experienced during the travel or shopping process (Hughes, 1995;Snepenger et al, 2003;Cary, 2004).…”
Section: Service Packages and Service Qualitymentioning
confidence: 99%